Youth Organizations’ Promotion of Education for Sustainable Development Competencies: A Case Study - Kieu, Thi Kinh; Singer, Jane (European Journal of Sustainable Development, 2020)
This paper details how two popular non-formal actors at Vietnamese universities, the Youth Union and youth environmental clubs, promote engagement by student teachers in sustainability. Though their activities were found to have enhanced students’ awareness of environment and sustainability, there remain two categories of constraints, internal and external, preventing students from proactive performance in sustainability. Based on an analysis of each organization’s strength and weaknesses, and on students’ demands, the authors suggest four steps to improve sustainability planning, including establishment of a hub of sustainability promotion, fostering sustainability leadership, conceiving a systematic action plan, and creating a communication network to promote students’ active efforts towards sustainability Keywords: youth, sustainability-linked activities, education for sustainable development